Clinical management of urolithiasis - Knoll, Thomas; Pearle, Margaret S. (Springer Berlin / Heidelberg, 2012)
With the incidence of urolithiasis rising worldwide, this vital addition to the literature is a practical guide for urologists on the diagnosis, management, and prevention of urinary calculi, ranging from new imaging procedures to interventional treatments.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Therapie; Harnsteinkrankheit